(untitled) (Vietnam Journal of Community Medicine, 2023)
Pneumonia is the disease with the highest mortality rate among infectious diseases. Identifying the cause of the disease helps to make treatment more effective and limit antibiotic resistance. Research objective: To identify the microbial pathogens causing pneumonia in children at the Pediatrics Department - Bach Mai Hospital in 2021. Methodology: A retrospective review of all inpatient pneumonia treatment records at the department of Pediatrics - Bach Mai Hospital, age from 0 months to 15 years old, meeting the criteria for definite diagnosis of pneumonia and having performed microbiological testing of nasopharyngeal swab samples satisfying the selection criteria and to exclude, to expel. Results: Through the results of a study of 208 pneumonia cases that met the access standards at the Pediatrics Department, Bach Mai Hospital in 2021, the detection rate of microbiological etiology was 50.8%, in which the microbial etiology was bacteria accounted for 44.0%; co-infection with 2 or more bacteria accounted for 6.7%. No viral or fungal etiology was detected. Among bacterial etiologies, 83.0% are typical bacteria, and atypical bacteria account for 3.0%. The most common bacteria groups were H. influenzae (51.9%), S. pneumoniae (24.6%) and M. catarrhalis (8.2%). Conclusion: The main cause of pneumonia in children is microbiological, in which mainly typical bacteria.